Qurban as Social Worship from Hadith Perspective: Qualitative Study - Rohadatul ‘Aisy; Asep Saiful Mimbar (Gunung Djati Conference Series, 2021)
This study aims to discuss the understanding of qurban from the perspective of hadith. This research is a qualitative type by applying literature study. The research was carried out by collecting library sources, both primary and secondary. The results and discussion of this study include the definition of qurban, the hadith about the command to sacrifice, the obligatory and legal requirements of qurban and the law of qurban. The conclusion of this study is that qurban is an activity of slaughtering livestock on Eid al-Adha as a form of getting closer to Allah and gratitude for the holiday, which has terms and conditions that apply and has laws that are sourced from hadith.